Genetic associations of the vitamin D and antiviral pathways with natural resistance to HIV-1 infection are influenced by interpopulation variability. (2019)
Vitamin D (VitD) may modulate anti-HIV-1 responses modifying the risk to acquire the HIV-1-infection. We performed a nested case-control exploratory study involving 413 individuals; HIV-1-exposed seropositives (cases) and seronegatives (HESN) (controls) from three cohorts: sexually-exposed from Colombia and Italy and parenterally-exposed from Spain. The association and interactions of 139 variants in 9 VitD pathway genes, and in 14 antiviral genes with resistance/susceptibility (R/S) to HIV-1 infection was evaluated. Associations between variants and mRNA levels were also analyzed in the Colombian samples. Variants and haplotypes in genes of VitD and antiviral pathways were associated with R/S, but specific associations were not reproduced in all cohorts. Allelic heterogeneity could explain such inconsistency since the associations found in all cohorts were consistently in the same genes: VDR and RXRA of the VitD pathway genes and in TLR2 and RNASE4. Remarkably, the multi-locus genotypes (interacting variants) observed in genes of VitD and antiviral pathways were present in most HESNs of all cohorts. Finally, HESNs carrying resistance-associated variants had higher levels of VitD in plasma, of VDR mRNA in blood cells, and of ELAFIN and defensins mRNA in the oral mucosa. In conclusion, despite allelic heterogeneity, most likely due to differences in the genetic history of the populations, the associations were locus dependent suggesting that genes of the VitD pathway might act in concert with antiviral genes modulating the resistance phenotype of the HESNs. Although these associations were significant after permutation test, only haplotype results remained statistically significant after Bonferroni test, requiring further replications in larger cohorts and functional analyzes to validate these conclusions.